UJI STABILITAS FISIK FORMULASI SEDIAAN HAIR TONIC HERBAL BUAH MENTIMUN (Cucumis Sativus L) SEBAGAI PERAWATAN RAMBUT - Komang Tri Musthika; Putu Indra Cyntia Dewi (Jurnal Penelitian Farmasi & Herbal, 2023)
Hair is an essential part of the body that often experiences various problems, one of which is hair loss. Fortunately, hair loss problems can be prevented by applying a hair tonic. Many hair tonic preparations are on the market, both made from herbal and synthetic ingredients. Efforts have been made to formulate cucumber into hair tonics. This study aims to utilize herbal plants, particularly cucumber, as a remedy for hair loss. Cucumber was developed into several hair tonic formulations, and their physical stability was subsequently tested. The cucumber was extracted using the infusion method. The yielded infusion was later made into three formulas of hair tonics with three times replications for each procedure. Following the formulations, physical stability tests of the preparations were carried out, such as organoleptic, homogeneity, pH, and viscosity tests. Results of the tests showed that the trials were physically stable with a homogenous physical appearance indicating an even distribution of cucumber extract in the preparations. Further results showed average pH of 5.87, 6.12, and 6.49 with viscosity values of 0.0082, 0.0083, and 0.0085 N.S/m2, respectively. In conclusion, all the ingredients in the formulation of herbal hair tonics provided stable color and pH range that still met the requirements. Hence, this study suggested the administration of cucumber hair tonic as one of many remedies for hair ailments, specifically hair loss.